Efeito do pacing e do exercício prévio na performance aeróbia - Reis, Daniela Charetti [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The aim of this study was to analyze the influence of prior exercise on different intensity distribution strategies (pacing). The study included five male individuals, apparently healthy, aged between 18 and 25 years, and without regular practice of physical activities. The subjects were tested on different days following the protocols on a cycle ergometer: 1) a progressive ramp test, 2) three constant load tests in the intensities of 85%, 90% and 95% IVO2max to exhaustion, and 3) six tests with and without holding a prior exercise intensity of 70%  with different strategies for Even-intensity pace, ES (401 ± 70 W), which consists of an exercise at a pace and / or constant intensity from beginning to end; where intensity is initially increased to 10% less than the ES progressively increase to reach 10% above the intensity of ES, and; Fast-start; FS, where there is a reversal in the way of distributing intensity, ie the initial intensity is 10% higher than the value of ES decreased progressively to 10% below that ES. All these tests were performed in random order. The tlim with previous exercise was significantly shorter than without previous exercise at FS condition (p < 0.05). The VO2final obtained at ES condition was similar with (3243 ± 599 ml.min-1) and without (3252 ± 384 ml.min-1) previous aerobic exercise (p > 0.05). However, the VO2final obtained at FS condition was higher with (3291 ± 218 ml.min-1) than without (3097 ± 207 ml.min-1) previous aerobic exercise (p < 0.05). The heart rate was higher at ES condition with than without previous aerobic exercise (p < 0.05). There was no significant difference in this variable for FS condition with and without previous aerobic exercise (p > 0.05). It can be concluded that the results the previous exercise (70%) achieved lasting 6 minutes followed by 6 minutes of recovery appears to influence / commit ting the conditions during the pacing for this population

O objetivo deste estudo foi analisar a influência do exercício prévio sobre diferentes estratégias de distribuição de intensidade (pacing). Participaram deste estudo 5 indivíduos do gênero masculino, aparentemente saudáveis, com idade entre 18 e 25 anos, e sem prática regular de atividades físicas. Os indivíduos foram submetidos, em dias diferentes aos seguintes protocolos no cicloergômetro: 1) 1 teste progressivo de rampa; 2) 3 testes de carga constante nas intensidades de 85%, 90% e 95% IVO2max até a exaustão e; 3) 4 testes com e sem a realização de um exercício prévio na intensidade de  70% com diferentes estratégias de intensidade Even-pace; ES, onde consiste em um exercício em um ritmo e/ou intensidade constante do começo ao fim; e; Fast-start; FS, onde há uma inversão na forma de distribuir a intensidade, ou seja a intensidade inicial é 10% maior que o valor de ES diminuindo progressivamente até atingir 10% abaixo que ES. Todos esses testes foram realizados em ordem aleatória. O tlim foi significantemente maior na condição FS (130 ± 19 s) em relação à condição ES (119 ± 21 s) somente na condição sem exercício prévio (p < 0,05). O tlim com exercício prévio foi significantemente menor do que sem exercício prévio na condição FS (p < 0,05). O VO2final obtido na condição ES foi similar com (3243 ± 599 ml.min-1) e sem (3252 ± 384 ml.min-1) o exercício aeróbio prévio (p > 0,05). No entanto, o VO2final obtido na condição FS foi maior com (3291 ± 218 ml.min-1, respectivamente) do que sem (3097 ± 207 ml.min-1) o exercício aeróbio prévio (p < 0,05). A frequência cardíaca foi maior na condição ES com do que sem o exercício prévio (p < 0,05). Não houve diferença nesta variável para as condições de FS com e sem exercício prévio (p > 0,05). Pode-se concluir que os resultados o exercício prévio ( 70%) ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Exercícios aeróbicos; Batimento cardíaco; Ciclismo; Modelos matematicos; Aerobic exercises; Heart beat; Cycling; Mathematical models